Effects of Feeding Patterns on Feed Intake, Nutrient Utilization and Volatile Fatty Acids in the Rumen of Crossbred Meat Goat - Boonrord, Katekanok; Kraiprom, Thaintip; Sapsiri, Sanalak; Pastsart, Umaporn (Recent Science and Technology, 2025)
The objectives of this research were to study the effects of feeding patterns on feed intake, nutrient utilization, and volatile fatty acids in the rumen of crossbred meat goat. Twenty male crossbred meat goats with an average initial body weight of 19.59±0.98 kg and age 3-4 months were used. The experimental design was an independent T-test conducted over a period of 90 days. The goad were divided into two groups: Group 1 was fed a TMR with a protein level of 16 percent, while Group 2 was fed a concentrate with the same protein level of 16 percent and fed Napier Pak Chong 1 grass ad libitum. The results showed that feed intake (CP, EE and Ash) and nutrient digestibility (OM, CP, EE, Ash, CF, NDF and ADF) of goats fed the TMR diets were significantly higher than those fed the separated diet (P<0.05). However, the feeding pattern had no effect on the volatile fatty acids in the rumen, which remained within the normal range of 42.61-54.08 mmol/L (P>0.05). In conclusion, feeding patterns affect feed intake and nutrient utilization but do not influence the concentration of volatile fatty acids in the rumen.